Translational stiffness and resistance of sandwich panel connections at elevated temperature. (1st February 2022) - Garifullin, Marsel; Shoushtarian Mofrad, Ashkan; Cábová, Kamila; Wald, František; Pasternak, Hartmut; Mela, Kristo
Highlights: Shear behavior of sandwich panel connections at elevated temperature is presented. 32 connections were tested experimentally at ambient and elevated temperature. A finite element model was developed and validated against test data. Analytical solutions for resistance and stiffness of connections are developed. The core material is the key parameter influencing the shear behavior of connections. Abstract: When sandwich panels are used as cladding structures, they contribute to the structural behavior of the building frame. In particular, sandwich panels can noticeably improve the stability of members as well as the global stability of the building. In the design calculations for stability, the properties of the connections between sandwich panels and the supporting steel members play a key role. Although guidelines exist for the resistance and stiffness of sandwich panel connections at ambient temperature, no such rules are available for the fire limit state. To bridge this gap, this study presents an investigation on the translational (shear) behavior of sandwich panel connections at elevated temperatures. A series of connection tests are reported, followed by the description of a numerical model of the analyzed connections. The numerical model is validated against the experimental results, and a parametric study is carried out to extend the scope of the considered connections and investigate the contribution of independent variables. Finally, analytical solutions for the translational resistance and stiffness of sandwich panel connections at elevated temperatures are proposed and verified against the obtained experimental and numerical results. The analytical solutions employ the existing rules for the behavior of connections at ambient temperature and consider several approaches to incorporate the effect of elevated temperature. The panels are considered with PIR and mineral wool cores, with the thickness in a range from 100 to 230 mm. The behavior of panels is analyzed at temperatures up to 600 °C.